Transport and noise properties of YBCO nanowire based nanoSQUIDs. (7th June 2019) - Trabaldo, E; Arpaia, R; Arzeo, M; Andersson, E; Golubev, D; Lombardi, F; Bauch, T
Abstract: The development of quantum limited magnetic flux sensors has recently gained a lot of attention for the possibility of detecting the magnetic moment of nanoscaled systems. Here, the ultimate goal is the observation of a single spin. Such sensors are of fundamental importance for applications, ranging from spintronics and spin-based quantum information processing, to fundamental studies of nano-magnetism in molecules and magnetic nanoclusters. A nano-scale superconducting quantum interference device (nanoSQUID) is indeed a promising candidate to reach this ambitious goal. Nanowires, fabricated of high critical temperature superconductors (HTS), have been shown to be a valid candidate for the realization of nanoSQUIDs. A crucial requirement to achieve the necessary flux sensitivity and spatial resolution, is a SQUID loop on the nanometer scale. Moreover, HTS nanowire-based SQUIDs in combination with large area pickup loops or flux transformers might become instrumental in magnetometer applications, such as magneto encephalography and low field magnetic resonance imaging, where low intrinsic magnetic field noise is required. In this review we will give a survey on the state of the art of YBa2 Cu3 O7− δ thin film nanowires and their implementation in low noise nanoSQUIDs and magnetometers.